The Techniques of Teaching Reading Comprehension at Second Grade Students at SMP Institut Indonesia - Tri Widiyanti; Amrin Batubara; Waode Hamsia (English Department FKIP Universitas Muhammadiyah Surabaya Indonesia, 2014)
The result of this study show that the English teacher used techniques SQ3R (survey or skimming, questioning, read, recall and review) and scanning in teaching. The implementation into students ability, the teacher used three-phase stages in reading they are: pre reading activity, whilst reading activity, and post reading activity. whereas the strength and weaknesses of the techniques, the teacher used the same techniques in teaching reading to make easier for students. It is to make student more attracted because the teacher always give them motivation in guidance and the teacher also help the students to increase their ability in pronunciation. Moreover, the researcher found in weaknesses of this technique sometimes the students felt bored because they got the same techniques used by the teacher. Therefore, it is suggested the teacher use these techniques in teaching reading comprehension, Finally the researcher suggested that the teacher should always give the motivation and the teacher combines the techniques so that the students can easily understand the lesson that the teacher teaches, it means that the teacher has made the students perform better in their learning activity.